Computational Fluid Dynamics Modeling of Gas‐Liquid Two‐Phase Flow around a Spherical Particle. Issue 5 (24th April 2013) - Du, W.; Feng, D.; Xu, J.; Wei, W.
Abstract Microscale studies, which can provide basic information for meso‐ and macroscale studies, are essential for the realization of flow characteristics of a packed bed. In the present study, the effects of gas velocity, liquid velocity, liquid‐solid contact angle, and liquid viscosity on the flow behavior were parametrically investigated for gas‐liquid two‐phase flow around a spherical particle, using computational fluid dynamics (CFD) methodology in combination with the volume‐of‐fluid (VOF) model. The VOF model was first validated and proved to be in good agreement with the experimental data. The simulation results show that the film thickness decreases with increasing gas velocity. This trend is more obvious with increasing operating pressure. With increasing liquid velocity, the film thickness tends to be uniform on the particle surface. The flow regime can change from film flow to transition flow to bubble flow with increasing contact angle. In addition, only at relatively high values does the liquid viscosity affect the residence time of the liquid on the particle surface.